1963
DOI: 10.1029/jz068i001p00055
|View full text |Cite
|
Sign up to set email alerts
|

Protons in the outer zone of the radiation belt

Abstract: The trapped protons in the outer zone of the Van Allen radiation belt were measured on October 4, 1960, by means of a Scout rocket payload containing a two‐crystal scintillation spectrometer. Protons with energies above 1 Mev were detected, the intensity rising above background at an altitude of 1200 km. Representative intensities for 1≤Ep≤0 Mev at 2, 3, 4, and 5 times; 03 km, through a range of 42°N to 30°N geomagnetic latitudes, were 0.27, 0.90, 2.02, and 4.56 times; 05 protons/cm2 sec ster. These intensitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1963
1963
1972
1972

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…The integral spectra given by Bame et al, (1963) and are very steep and agree relatively well with the spectra derived in this work, allowing for the different locations and the accuracy of the measurements.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The integral spectra given by Bame et al, (1963) and are very steep and agree relatively well with the spectra derived in this work, allowing for the different locations and the accuracy of the measurements.…”
Section: Discussionsupporting
confidence: 76%
“…These levels seem to be lower by about a factor of ten than the present data, although the different locations of the measurements as well as variations in the outer zone may account for the difference. Bame et al, (1963) give an intensity of -5 x 10 5/cm 2sec ster for protons above -1 Mev at L a 2. 5…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Since the discovery of the low-energy (•1 Mev) protons by Bame et al [1962] and Davis and Williamson [1963], many measurements have been reported for the spatial distribution, energy spectrums, pitch-angle distributions, etc., particularly in the steady state. (For a recent review see Williams [1970].)…”
mentioning
confidence: 99%